Porcine Circovirus Type 2 ORF5 Protein Induces Autophagy to Promote Viral Replication via the PERK-eIF2α-ATF4 and mTOR-ERK1/2-AMPK Signaling Pathways in PK-15 Cells - Lv, Jiangman; Jiang, Yanfen; Feng, Quanwen; Fan, Zhixin; Sun, Ying; Xu, Panpan; Hou, Yufeng; Zhang, Xiuping; Fan, Yuxin; Xu, Xingang; Zhang, Yanming; Guo, Kangkang (Frontiers in Microbiology, 2020)
Porcine circovirus type 2 (PCV2) is the primary causative agent that causing porcine circovirus-associated disease (PCVAD). The open reading frame 5 (ORF5) protein is a newly discovered non-structural protein in PCV2, which the function in viral pathogenesis remains unknown. The aim of this study was to investigate the mechanism of PCV2 ORF5 protein on autophagy and viral replication. The pEGFP-tagged ORF5 gene was ectopic expressed in PK-15 cells and an ORF5-deficient PCV2 mutant strain (PCV2ΔORF5) were used to infected PK-15 cells. This study demonstrated that the ORF5 is essential for the of PCV2-induced autophagy. The ORF5 protein triggers the phosphorylation of PERK, eIF2α and the expression of downstream transcription factor ATF4. In addition, ORF5 protein activated the AMPK-ERK1/2-mTOR signaling pathways. These findings suggest that ORF5 play essential roles in the induction of autophagy by PCV2. We further revealed that PCV2 ORF5 promotes viral replication through PERK-eIF2α-ATF4 and AMPK-ERK1/2-mTOR pathways. In conclusion, we showed that PCV2 ORF5 induces autophagy to promote virus replication in PK-15 cells.